ANALISIS YURIDIS SISTEM PEWARISAN DALAM PERKAWINAN ANTAR SUKU PADANG DAN SUKU MELAYU (STUDI DI KOTA MEDAN) - RICHI WAPTI SYAIFHAS (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Muhammad Yamin, SH, MS, CN2.  Prof. Dr. Hasim Purba, SH, MHum3.  Dr. Rosnidar Sembiring, SH, MHumThis research is done in Kelurahan Kota Matsum III, Medan. Many Minangkabaunese are married with the Melayunese in this research area. The research problems are about which inheritance system is applied in a marriage between the Minangkabaunese and the Melayunese ( a case study in Kelurahan Kota Matsum III, Medan), how inheritance is split to the children of the marriages , and how inheritance is split to the widow of the marriages. This thesis employs empirical juridical research type with descriptive analysis. It uses primary data collected from interviews with the people having marriages between the Minangkabaunese and the Melayunese and with the traditional leaders. It also uses secondary data consisting of primary legal materials such as Compilation of Islamic Laws and Marriage Act, secondary legal materials such books, and tertiary legal materials such as dictionaries.Keywords: Inheritance, Minangkabaunese, Melayunese.